Using fingers method to overcome students problems in subtraction with regrouping / Tuah Ogeemin - Ogeemin, Tuah (2015)
Problems among students in Mathematics is a serious concern. Therefore, researchers have chosen a very important basic skills in Mathematics Year Two in subtraction with regrouping. Various types of errors can be done by students. Hence, this thesis is to analyze student achievement data before and after they are taught using Fingers Method and to see whether the method that introduced can increase the students mastery in subtraction with regrouping. Eight participants in the study were selected based on their weak performance in the last mid-year examinations. The instrument was used to collect the data is including questionnaire, pre-test, post test and interview by Newman Error Analysis Procedures that have been modified by researchers to suit the subtraction with regrouping. Through this interview, respondents mentored individually by using Method Finger for four weeks. Pre-test was conducted to assess the beginning level of the respondents achievement in the study before Fingers Method was introduced to them. After that, the respondents have called for interviews individually to identify the cause of their weakness and mentored directly by using Fingers Method. During the guidance is given, all types of students weaknesses have been recorded in Form Types of individual Weaknesses in the Subtraction With Regrouping. Post-test was administered to assess the achievement of the respondents after the completion of the guidance given. A comparison between pre-test and post test for all respondents have shown a 100% increase in performance. This clearly proves the Fingers Method that has been introduced to respondents were succeeded in increasing the performance of respondents in subtraction with regrouping.